Pengaruh Pertumbuhan Penduduk, Ketimpangan Pendapatan, dan Pengangguran terhadap Tingkat Kemiskinan di Kalimantan Selatan - Yolanda Mahrita Sari; Chairul Sa’roni (PPJP ULM, 2020)
This Study was conducted to (1) Analyze population growth, income inequality,and unemployment simultaneously on poverty levels from 2011 till 2017. (2) Analyze thevariables that are most dominantly affecting poverty levels. This research usedsecondary data and quantitative. In this study, data generated were sourced from theCentral Statistics Agency from districts/cities in South Kalimantan in 2011-2017. Dataanalysis technique using data panel regression analysis with random effect models. Thisstudy's results based on panel data regression analysis showed all independentvariables jointly had a significant effect on poverty levels in South Kalimantan's 13districts/cities.